Multi-objective hybrid flow shop scheduling with variable discrete production speed levels and time-of-use energy prices - Sven Schulz; Udo Buscher; Liji Shen (Journal of Business Economics, 2020)
Energy costs play an important role in industrial production and are closely related to environmental concerns. As sustainability aspects are coming into focus in recent years, energy-oriented objectives are increasingly being taken into account in scheduling. At the same time, requirements for punctual delivery become more and more important in times of just-in-time delivery and highly networked supply chains. In this paper, a hybrid flow shop scheduling problem with variable discrete production speed levels is considered with the aim of minimizing both energy costs and total tardiness. Although lower speeds can reduce energy consumption, they also increase processing times, which counteract the objective of punctual delivery. Two new model formulations additionally taking time-of-use energy prices into account are presented and compared. The influence of variable discrete production speed levels on energy costs, energy consumption and punctual delivery as well as the interdependencies between these objectives are analysed in a numerical case study.
Keywords: C30; C61; Q41; 650; Energy efficient scheduling; Hybrid flow shop; Mixed integer programming; Sustainability; Multi-objective optimization